UXUC - User experience & urban creativity scientific journal, vol.3, nº2 (2021) - Erdi, Gülçin (2022)
This special issue grew out of a two day conference entitled Whose space is it? Interstices and urban commons: the city from an interdisciplinary perspective, which was held at the University of Tours in December 2020. Despite of difficult conditions and impredictibality of situation due to Covid-19 pandemic, the conference was a real success and brought together researchers from various disciplines of social science and more than ten countries. This conference provided an excellent venue within which to begin the discussions on the signification, the use and the ways of appropriation of what is called urban interstices covered in this issue. Urban interstices were one of the two main research themes of this conference whose scientific purpose has been collectively prepared by myself, Bénédicte Florin and Ulrike Krampl, all of us from University of Tours. The interesting point was to see how our different scientific disciplines, respectively sociology, geography and history provided a large scope to understand the interstices and their perception.